Análise dos impactos da Lei de Uso e Ocupação do Solo nas desigualdades da acessibilidade às atividades em Fortaleza - Aragão, Amélia de Andrade (2021)
The disconnect between land use planning and transport has been identified as one of the main factors for the low levels of accessibility to basic activities in urban centers. Studies confirm a mutual influence between accessibility and land use, with the diversity of uses being one of the elements pointed out as of great importance in this relationship. Considering urban laws as a fundamental instrument in the planning of Brazilian cities, and their roles as paradigmatic mirrors of the dominant thought at the time of their elaboration, this research adopts the Lei de Uso e Ocupação do Solo de Fortaleza (LUOS) [Law of Land Use and Occupation of Fortaleza] as one of its main objects of study. This Law consists of one of the most important instruments for the regulation of land use in the Municipality and is probably the product of planning that most influence its diversity. This dissertation had the following objectives, therefore: to analyze conceptually the relations between the diversity of land use and accessibility to activities in urban areas; discuss the LUOS instrument, defining its scope and importance as a planning tool, as well as its potential influence on urban morphology; and, finally, to assess the impacts of LUOS in Fortaleza (1996) on the diversity of land uses and inequalities in accessibility to activities over the city territory. To achieve these objectives, a literature review was initially done, addressing studies focused on the relationship between accessibility and the diversity of land uses. The afore mentioned studies indicated that accessibility and diversity are closely connected factors and that they exert mutual influence. Then, LUOS de Fortaleza (1996) was presented and its main aspects were discussed about the potential impact on the city's land use, allowing the raising of hypotheses about the phenomenon under study. Finally, the hypotheses of relationships between LUOS and the resulting aggregated patterns of diversity and accessibility were investigated by means of indicators capable of measuring them, complemented by exploratory diagnostic analyzes of its patterns of spatial dependence verified in the city. It is believed that, based on the analyzes made, LUOS interfered in the diversity of land uses in Fortaleza, contributing to an inequality in diversity between zones, which consequently affected the inequality of accessibility to activities in the zones between different socioeconomic groups.